Early development of Rutilus frisii kutum kamenskii larvae with emphasis on the ontogeny of digestive tract - Jafari, Mahdieh (2011)
A series of experiments on the early development of Caspian kutum (Rutilus frisii kutum) larvae including the morphological and histological development of mouth and gut were conducted to determine the suitable feed type and size for the kutum larviculture and fry production on the basis of their morphological features. The embryonic and larval development of kutum were studied under hatchery conditions at 14-16º C using eggs were obtained through induced spawning of broodstock. Samples were taken every hour during the fertilization for two days and then six times per day till hatching (9 days). After hatching, daily observations were made until the fingerling stage. Nine main stages (zygote, cleavage, morula, blastula,gastrula, neurula, segmentation, pharyngula and hatching) and 30 sub-stages were observed during the embryonic development of kutum while three main stages and eighteen sub-stages were noted after the hatching until the juvenile stage. The mouth and gut development were monitored using light microscopy after haematoxylineosin (H&E) staining. The larvae were first fed with egg yolk for 5 days and followed with Artemia nauplii and egg yolk until the end of 30-days. Ten to twenty larvae were daily sampled from hatching to 3 days after hatch (DAH) and thereafter at every 3 days until 30 days. The larval mouth opened at 3 DAH and the mouth size was 145 ± 15.01 μm at 90º opening. A strong linear relationship between mouth size and total length was established. The digestive system was made of an undifferentiated straight tube at hatch and the system became sectioned into buccopharynx, oesophagus and intestine as the larva grew. Goblet cells in oesophagus were observed at 5 DAH and increased in number between 7 to 15 DAH. The first goblet cells appeared in the intestine at 7 DAH and increased in number and became abundant with the differentiation of intestinal mucosa from 10 to 20 DAH. A swimbladder was connected to the oesophagus via a pneumatic duct which can be seen from 1 DAH. Liver and pancreas were observed at 2 DAH and their ontogenetic changes were observed during the larval growth. The effects of diets on histological changes in digestive tract, growth, survival, body composition and digestive enzyme activities of kutum larvae were also studied. Larvae were fed for 30 days on three diets (egg yolk, Artemia nauplii, Artemia plus egg yolk) and starved in triplicates. No significant histological differences were observed in the intestine development of larvae at 5, 10 and 15 days among the feeding larvae. Starved larvae had smaller size and shape intestine. Larvae fed with Artemia plus egg yolk had significantly higher (P<0.05) final mean total length and body weight (28.6 ± 0.18 mm and 74 ± 3.64 mg, respectively) and the highest survival rate (70.9 ± 2.1%). The activities of digestive enzymes were detected at the start of exogenous feeding. Protease activity increased with growth after 21 DAH. Specific pepsin content peaked between 5-7 DAH and then decreased in all treatments. No significant differences in total chymotrypsin activity were observed between larvae fed on Artemia and egg. The total lipase activity generally increased with the larval development. These findings suggested that Caspian kutum larvae should be able to ingest, digest and absorb food particles within 50- 100 μm Ø from 3 DAH onwards. The functional alimentary tract of kutum larvae was completed by the 30 DAH. A combination diet of Artemia and egg yolk was the best for the culture of kutum during early life stages. Further studies on the larval feed development should be conducted to improve the production and quality of kutum fry.